2016
DOI: 10.1001/jamadermatol.2016.2503
|View full text |Cite
|
Sign up to set email alerts
|

High-grade Dysplasia in Anogenital Warts of HIV-Positive Men

Abstract: IMPORTANCE Human papillomavirus (HPV)-induced anogenital lesions are very frequent in men who have sex with men (MSM) who are HIV-positive (HIV+). Anogenital warts (AGWs) are considered benign lesions caused by low-risk HPV-types, whereas anogenital dysplasias are potential cancer precursors associated with high-risk HPV-types. Both types of lesions can usually be distinguished clinically. OBJECTIVE To describe a case series of HIV+ MSM with typical AGW that harbored different grades of dysplasia. DESIGN, SETT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Three societies have specifically identified HIV-positive patients with anogenital condylomas as a risk group for screening [17,19,23]. Several studies have described that a significant percentage of anal condylomas in HIV-positive patients harbor high-grade lesions [38][39][40][41]. Individuals with condylomas also have a long-term increased risk of HPV-associated anogenital cancers [42].…”
Section: Discussionmentioning
confidence: 99%
“…Three societies have specifically identified HIV-positive patients with anogenital condylomas as a risk group for screening [17,19,23]. Several studies have described that a significant percentage of anal condylomas in HIV-positive patients harbor high-grade lesions [38][39][40][41]. Individuals with condylomas also have a long-term increased risk of HPV-associated anogenital cancers [42].…”
Section: Discussionmentioning
confidence: 99%
“…The larger published study that included 319 HIV-positive and -negative patients submitted to anogenital wart surgical excision, found that in HIV-positive MSM, occult HSIL/cancer was found in 47, and 26% of HIV-negative MSM [16]. Other studies have reported a similar high trend [17-19]. …”
Section: Anal Wartsmentioning
confidence: 94%
“…However, condylomata acuminata indicate persistent HPV infection and therefore show an association with anal malignancy as discussed above. Moreover, recent data demonstrated high-grade lesions in genital warts including early cancer [39]. The cytological examination follows the revised Bethesda classification from 2001 [40].…”
Section: Pathological Classification Of Anal Neoplasmsmentioning
confidence: 99%